First case of acute cholestatic hepatitis attributed to oseltamivir in a young girl with ah1n1 influenza - Mastroianni, A.; Greco, S.; Vangeli, V.; Ritacca, R.; Mauro, M. V.; Guadagnino, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Oseltamivir caryboxylase is a potent inhibitor of the enzyme neuramidase of the influenza virus particle and it is active against both influenza A and B viruses. Oseltamivir is indicated for therapy or post-exposure prevention of influenza A and B. Side effects are uncommon and include mild nausea, gastrointestinal upset, dizziness and headache. Despite its widespread use, oseltamivir has not been associated with clinically apparent liver injury. To the best of our knowledge, this is the first case report in the literature linking the development of acute hepatitis to the consumption of oseltamivir in a patient suffering from influenza H1N1 infection.